Latitudinal gradient of cyanobacterial diversity in tidal flats - Vogt, Janina C. (PLoS One, 2019)
Latitudinal diversity gradients are well-known for plants and animals, but only recently similar patterns have been described for some specific microbial communities in distinct habitats. Although microbial diversity is well-investigated worldwide, most of the studies are spatially too restricted to allow general statements about global diversity patterns. Additionally, methodological differences make it hard and often impossible to compare several studies. This study investigated the cyanobacterial diversity in tidal flats along geographical and ecological gradients based on high-throughput sequencing of 16S rRNA gene fragments (Illumina MiSeq) and environmental data on a large spatial scale from the subtropics to the Arctic. Latitude and strongly correlated environmental parameters (e.g. temperature) were identified as important drivers of cyanobacterial diversity on global scale resulting in a latitudinal diversity gradient similar to that known from plants and animals. Other non-correlated parameters (e.g. grain size) were shown to be more important on local scales, although no consistent pattern occurred across different locations. Among a total number of 989 operational taxonomic units (OTUs) only one cosmopolitan (classified as Coleofasciculus chthonoplastes), but many location-specific and putative endemic ones (78%) were detected. High proportions of rare members of the community (up to 86%) were found in all samples. Phylogenetic beta diversity was shown to be influenced by the developmental stage of the mat community becoming increasingly similar with increasing stabilization.